Microdosimetric spectra simulated with MCNP6.1 with INCL4/ABLA model for kerma and mean quality factor assessment, for neutrons between 100 keV to 19 MeV. (September 2019) - Antoni, Rodolphe; Bourgois, Laurent
Abstract: From the application of the microdosimetric approach in dosimetry, the standard TEPC, i.e., Rossi-type detector, was found to be a well-suited device to measure "first collision" neutron kerma and develop lineal energy spectra for incident neutrons. Subsequently, several attempts were carried out to assess the ambient dose equivalent for neutrons, with a mixed outcome, through the evaluation of the mean quality factor. The ICRU report 63, released in 2000, has officially recognized a good agreement between theoretical Kerma factor and value measured with standard TEPCs for neutron energies ranging over 5–66 MeV. As a follow-up, benchmark with simulated results for Kerma calculation and lineal energy spectra concluded to a satisfactory agreement for Monte-Carlo transport codes such as FLUKA or GEANT4. Nevertheless, previous studies have highlighted major discrepancies with MCNP results for energy above the capture threshold, mainly stemming from the weakness of the alpha release. This paper emphasizes the improvement of the kerma factor calculation as well as the development of lineal energy spectra from a standard A150 plastic-wall TEPC with MCNP6.1. The shortcomings of the alpha release are overcome using INCL4/ABLA implementation instead of the default model for the Intra-nuclear cascade. This new approach lead to lineal energy spectra overlapping those from experiments. In addition, the neutron kerma is evaluated with a mean relative deviation not exceeding 5% of the ICRU standard values, for mono-energies from 100 keV to 19 MeV. This new approach is also relevant for usual neutron sources as AmBe and 252 Cf with a maximum deviation of roughly 6%. Nevertheless, major discrepancies remain for evaluation of the quality factor at the depth of 10 mm inside de ICRU sphere, with a mean relative deviation of 17%. However, this finding is consistent with discrepancies in literature. As regards the prospects, satisfactory results on lineal energy spectra and kerma evaluation henceforth offers the possibility to simulate microdosimetric spectra and determine neutron kerma for energies higher than a hundred keV up to twenty MeV. Highlights: Feasibility of calculating the kerma factor with TEPC detector for neutrons from 100 keV to 19 MeV with MCNP6.1. Feasibility of performing microdosimetric spectrum for monoenergetic neutrons and neutron spectra with MCNP6.1. Improvement provided by the implementation of the intranuclear cascade model INCL4/ABLA to simulate the alpha release by capture reaction in MCNP6.1.